Extracranial internal carotid artery vasospasm during thrombectomy. Issue 3 (June 2018) - Miura, Isamu; Kawashima, Akitsugu; Hayashi, Masataka; Tanda, Akane; Ishikawa, Tomomi; Kawamata, Takakazu
The use of a stent retriever increases the risk of intracranial vasospasm. Here, we report the case of a man who developed severe vasospasm in a long segment of the extracranial internal carotid artery after mechanical irritation by a stent retriever inserted for the treatment of acute cerebral ischemia. A 47-year-old right-handed man presented with sudden-onset right-sided weakness and difficulty speaking. The patient's National Institutes of Health Stroke Scale score was 6 and he had an Alberta Stroke Program Early Computed Tomography Score of 9. The patient was started on intravenous alteplase therapy, and an acute thrombectomy was performed. Left internal carotid digital subtraction angiography showed narrowing of the left common and internal carotid arteries and occlusion of the proximal left M1 segment of the middle cerebral artery. A stent retriever was retracted into a guiding catheter placed at the left carotid bulb under continuous suction. Recanalization of the middle cerebral artery was not achieved and there was significant narrowing in a long segment of the extracranial internal carotid artery associated with exacerbation of the patient's aphasia. The cervical vasospasm improved after nicardipine infusion via the catheter. We encountered vasospasm in a long segment of the extracranial internal carotid artery after mechanical irritation by a stent retriever. If a stent retriever is used in a patient with a narrow extracranial internal carotid artery, consideration should be given to using a Penumbra or smaller guiding catheter located in the distal internal carotid artery to prevent irritation to the cervical vessel wall.